Converting tropical forests to agriculture increases fire risk by fourfold. (1st October 2022) - Trancoso, Ralph; Syktus, Jozef; Salazar, Alvaro; Thatcher, Marcus; Toombs, Nathan; Wong, Kenneth Koon-Ho; Meijaard, Erik; Sheil, Douglas; McAlpine, Clive A
Abstract: Deforestation exacerbates climate change through greenhouse gas emissions, but other climatic alterations linked to the local biophysical changes from deforestation remain poorly understood. Here, we assess the impact of tropical deforestation on fire weather risk—defined as the climate conditions conducive to wildfires—using high-resolution convection-permitting climate simulations. We consider two land cover scenarios for the island of Borneo: land cover in 1980 ( forest scenario ) and land cover in 2050 ( deforestation scenario ) to force a convection-permitting climate model, using boundary conditions from ERA-Interim reanalysis for the 2002–2016 period. Our findings revealed significant alterations in post-deforestation fire precursors such as increased temperature, wind speed and potential evapotranspiration and decreased humidity, cloud cover and precipitation. As a result, fire weather events that would occur once a year in the forested scenario, are likely to occur four times a year following deforestation. Likewise, for extreme conditions, such as those occurring on longer time-horizons than 20 years, the magnitude of extreme fire weather is likely to double following deforestation. These increases in extreme fire weather conditions demonstrate the key role of tropical forests in regulating regional climate processes, including reduced fire weather risk.